Properties of Cosmic Lithium Isotopes Measured by the Alpha Magnetic Spectrometer - Aguilar, M. (AMER PHYSICAL SOC, 2025)
We present the first measurement of cosmic-ray fluxes of Li-6 and Li-7 isotopes in the rigidity range from 1.9 to 25 GV. The measurements are based on 9.7 x 10(5) 6Li and 1.04 x 10(6) 7Li nuclei collected by the Alpha Magnetic Spectrometer on the International Space Station from May 2011 to October 2023. We observe that over the entire rigidity range the Li-6 and Li-7 fluxes exhibit nearly identical time variations and, above similar to 4 GV, the time variations of Li-6, Li-7, He, Be, B, C, N, and O fluxes are identical. Above similar to 7 GV, we find an identical rigidity dependence of the Li-6 and Li-7 fluxes. This shows that they are both produced by collisions of heavier cosmic-ray nuclei with the interstellar medium and, in particular, excludes the existence of a sizable primary component in the Li-7 flux.